Subjective Happiness Among Polish and Hadza People - Frackowiak, Tomasz; Oleszkiewicz, Anna; Butovskaya, Marina; Groyecka, Agata; Karwowski, Maciej; Kowal, Marta; Sorokowski, Piotr (Frontiers in Psychology, 2020)
Life satisfaction and happiness were broadly studied in Western populations, whereas evidence from traditional societies remains surprisingly scarce. We collected data on the happiness from 145 Hadza, and compared it with data obtained from 156 Poles, representing Westernized society. Participants were asked to answer four simple questions from Subjective Happiness Scale (Lyubomirsky & Lepper, 1999). Results indicate that Hadza report a higher level of happiness with their lives than do Polish people. Our findings also show that sex was not related to happiness in both populations, while age was a negative predictor of happiness, but only among Poles. Therefore, we hypothesize that positive perception of aging in societies may increase their actual happiness.